2015
DOI: 10.1016/j.jdeveco.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Resource concentration and civil wars

Abstract: a b s t r a c tThis paper highlights the importance of natural resource concentration and ethnic group regional concentration for ethnic conflict. The existence of multiple conflict terrains (and hence multiple threat points) is the source of bargaining failure, similar to the one determined by the presence of offensive advantages. The theory predicts war to be more likely when resource concentration and group concentration are high, and the empirical analysis, both at the country level and at the ethnic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…21 Clearly there are many interesting features of political institutions from which we are abstracting, and there is no operational difference between a majoritarian oligarchy or a democracy in our analysis. 22 It is in the specification of the strategy set S 1 where our work deviates significantly from Morelli and Rohner (2014), they do not allow for the costless division of the country by the ruling group, and do require that if the ruling group engage in appropriation that they must simultaneously engage in conflict. in a secessionist civil war.…”
Section: Ii2 the Simple Dissolution Gamementioning
confidence: 99%
See 1 more Smart Citation
“…21 Clearly there are many interesting features of political institutions from which we are abstracting, and there is no operational difference between a majoritarian oligarchy or a democracy in our analysis. 22 It is in the specification of the strategy set S 1 where our work deviates significantly from Morelli and Rohner (2014), they do not allow for the costless division of the country by the ruling group, and do require that if the ruling group engage in appropriation that they must simultaneously engage in conflict. in a secessionist civil war.…”
Section: Ii2 the Simple Dissolution Gamementioning
confidence: 99%
“…14 In our analysis the prize is a pure public good, and it is conflict over 9 See Robinson (2000Robinson ( , 2001, Conley and Temimi (2001), Jack andLagunoff (2004, 2006) and Llavador and Oxoby (2004) for further analyses of the extension of the franchise. 10 In an interesting recent paper Morelli and Rohner (2014) consider a model in many ways similar to our own. However, their focus is on how the distribution of natural resource wealth effects the likelihood of civil war.…”
mentioning
confidence: 99%
“…The theoretical literature on natural resources and conflict aims to distinguish the channels that make resource windfalls raise the risk of armed fighting. In particular, it has been argued that (1) resource revenues drive up the motivation for investing in fighting by increasing the "pie" that is up for appropriation (recent work includes Caselli and Coleman 2013; Esteban, Morelli, and Rohner 2015; Rohner, Thoenig, and Zilibotti 2013a); (2) resource abundance box continues next page weakens state capacity because the state has less incentive to build legal and fiscal capacity (Besley and Persson 2011;Fearon 2005); (3) capturing resource rents relaxes rebels' borrowing constraints and makes armed rebellion financially feasible (Berman and others 2015;Collier, Hoeffler, and Rohner 2009;Fearon 2004;Guidolin and La Ferrara 2007;Nunn and Qian 2014); and (4) the unequal geographic distribution of natural resource deposits fuels the risk of secessionism and interstate wars (Caselli, Morelli, and Rohner 2015).…”
Section: Box 24 Natural Resources and Conflictmentioning
confidence: 99%
“…The empirical literature on natural resources and conflict has shown that the outbreaks and duration of conflicts are linked to the abundance of primary commodities in general (Collier and Hoeffler 2004;Collier, Hoeffler, and Rohner 2009); the presence of oil and natural gas (Dube and Vargas 2013;Fearon and Laitin 2003;Humphreys 2005;Lei and Michaels 2014;Morelli and Rohner 2015;Ross 2006), and deposits of diamonds and precious minerals (Aragon and Rud 2013; Berman and others 2015;Humphreys 2005;Lujala, Gleditsch, and Gilmore 2005;Ross 2006).…”
Section: Box 24 Natural Resources and Conflictmentioning
confidence: 99%
“…Third, my paper is also related to theoretical contributions on the effects of a country's ethnic composition on the political struggle for power (e.g., Caselli and Coleman 2013;Esteban andRay 2008, 2011;Hodler 2006;Morelli and Rohner 2015). Some of these contributions also focus on how the interplay between ethnic composition and natural resource revenues shapes this struggle, but they look neither at political transitions and regime changes, nor at the role of political leaders and their ethnic or religious group affiliation.…”
mentioning
confidence: 99%